EFFECT OF VARYING DIETARY LEVELS OF CALCIUM AND PHOSPHORUS ON APPARENT DIGESTIBILITY AND RETENTION OF MACRO AND MICRO-MINERALS IN LACTATING SAHIWAL COWS - M. Z. U. Khan; T. N. Pasha; K. Javed; M. J. Basra; M. A. Jabbar (Journal of Animal and Plant Sciences, 2020)
Overfeeding or underfeeding of minerals to the animals may affect health of dairy animals and cost of production. The objective of this study was to investigate the impact of varying dietary levels of Ca and P on apparent digestibility and retention of Ca, P, Mg and Zn. For this purpose, 36 second parity Sahiwal cows at peak lactation stage averaging 70±10 days in milk (DIM) were offered one of six different treatments of varying levels of Ca and P (NCP = Normal Ca and P, HP = 40% higher P, LC = 40% lower Ca, LCHP = 40% lower Ca and 40% higher P, HC =40% higher Ca, or HCHP = 40% higher Ca and P) following a Completely Randomized Design. Dietary Ca and P levels and their ratios did not affect (P>0.05) daily milk yield. Feeding higher than recommended Ca levels (HC, HCLP, HCHP) resulted in a significant decrease (P < 0.05) in apparent Ca digestibility and retention and a significant decrease (P < 0.05) in apparent Zn digestibility. Feeding higher than recommended P resulted in a significant decrease (P < 0.05) in apparent P digestibility, irrespective of dietary Ca levels. Dietary P levels did not (P > 0.05) affect apparent Zn digestibility. A decrease (P < 0.05) in apparent digestibility of Mg was observed in treatment groups HC and HCHP.
Keywords: Calcium; phosphorus; magnesium; varying levels; apparent digestibility